2005
DOI: 10.1103/physrevb.71.155313
|View full text |Cite
|
Sign up to set email alerts
|

Spin-dependent resonant tunneling in symmetrical double-barrier structures

Abstract: A theory of resonant spin-dependent tunneling has been developed for symmetrical double-barrier structures grown of non-centrosymmetrical semiconductors. The dependence of the tunneling transparency on the spin orientation and the wave vector of electrons leads to (i) spin polarization of the transmitted carriers in an in-plane electric field, (ii) generation of an in-plane electric current under tunneling of spin-polarized carriers. These effects originated from spin-orbit coupling-induced splitting of the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(69 citation statements)
references
References 16 publications
0
69
0
Order By: Relevance
“…Using such an experimental setup, one could obtain large spin polarization following the procedure of Perel et al 7 and Glazov et al 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Using such an experimental setup, one could obtain large spin polarization following the procedure of Perel et al 7 and Glazov et al 9 .…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by [1] for the single-barrier and by [2] for the double-barrier structure shown in Fig. 1., Eq.…”
Section: The Double-barrier Resonant Structure and Nonparabolicitymentioning
confidence: 99%
“…Glazov et al [2] have shown that the transmitted electrons generate a spin polarized current if an in-plane electric field is applied to a double-barrier resonant tunnelling structure (DB-RTS). In our previous work, we have discussed that significant spin-polarization may be expected in both asymmetric DB-RTSs and symmetric triple-barrier structures [3,4] with the the influence of the perpendicular electric field proven to be particularly important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Furthermore, resonant tunneling diodes (RTDs) are interesting devices for studying the physical properties of 2D systems due to the fact that their carrier density and the resulting parameters, such as the filling factor, can be varied by the applied bias voltage. [12][13][14][15][16][17][18][19][20][21] Several previous works have shown that 2DHG formed in the accumulation layer can inject spin-polarized holes in the quantum well (QW) region and make an important contribution to the spin polarization of carriers in resonant tunneling diodes. 21 In this paper, we have investigated the effect of the electric field and laser excitation intensity on the spin properties of 2DHGs formed at the accumulation layer next to the emitter barrier of a ptype GaAs/AlAs resonant tunneling diode.…”
Section: Introductionmentioning
confidence: 99%